(untitled) (Scientific journal of the Fergana State University, 2023)
In the work a problem with shift conditions for a second kind degenerated hyperbolic type equation has been formulated and unique solvability of the considered problem has been investigated. The solution of the problem was found by using general solution of the equation. The problem was reduced to an integral equation with respect to trace of the unknown function. During the investigation of the problem the properties of Gauss’s hyperheometric function and symbol of Pochhammer have been used